Analysis of Cargo Transportation and Organization of Transport Logistics of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2018)
In the Address to the People, the President of the Republic of Kazakhstan noted seven keyclusters that determine the long-term specialization of the economy in non-resource sectors.Among them, transport logistics is noted, which in the future should adequately meet the needsof the economy and the population in freight transport and successfully compete in world markets.Transport is an important part of the market infrastructure and economic base of the state as a whole. The purpose of the study is to analyze the freight transport logistics and organization ofthe country. In the Kazakhstan market, one of the most common branches of the transport systemis rail transport. For transportation of passengers and cargoes of “NC” JSC “ Kazakhstan Railway“uses rolling stock and other railway wagons inventory administrations and the private rollingstock operating companies. In this article, the structure of the railroad railroads in the interconnectedand exporting sectors is represented. The analysis of the dynamics of the main indicators ofthe transport logistics of the country: freight turnover and passenger turnover. The main problemsin the logistics industry of the Republic of Kazakhstan are considered. The standards of transportlogistics of Kazakhstan are given. Currently, the state plans a full-scale realization of the transitpotential of Kazakhstan, the opening of the new railways. The works on the Kazakhstan section ofthe large-scale transport corridor Western China – Western Europe are being completed. Formationof high-tech international transport corridors “West-East”, “South-North” dictates the need tocreate powerful regional traffic control centers.